2022
DOI: 10.1021/acsami.2c14435
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability, Strong Four-Phonon Scattering, and Low Lattice Thermal Conductivity in Superatom-Based Superionic Conductor Na3OBH4

Abstract: Superatom-based superionic conductors are of current interest due to their promising applications in solid-state electrolytes for rechargeable batteries. However, much less attention has been paid to their thermal properties, which are vital for safety and performance. Motivated by the recent synthesis of superatom-based superionic conductor Na3OBH4 consisting of superhalogen cluster BH4, we systematically investigate its lattice dynamics and thermal conductivity using the density functional theory combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…73 However, among non-CST materials, and even compared to previously reported Ag-based thermoelectrics 71,[76][77][78] Pb-containing Ag 2 PbGeS 4 stands out with a k L value of approximately 0.15 W m −1 K −1 at 300 K. This value is lower than that of Cu 4 TiSe 4 (k L z 0.19 W m −1 K −1 ), which is getting close to the amorphous limit of lattice thermal conductivity. 79 The inclusion of additional four-phonon scattering rates 80 and considering various other phonon scattering mechanisms may further reduce the calculated k L within this family of compounds. Therefore, the amorphous k L and anharmonic nature of these materials necessitate a particle-like phonon treatment, 81 an exciting topic for future research.…”
Section: Lattice Thermal Transportmentioning
confidence: 99%
“…73 However, among non-CST materials, and even compared to previously reported Ag-based thermoelectrics 71,[76][77][78] Pb-containing Ag 2 PbGeS 4 stands out with a k L value of approximately 0.15 W m −1 K −1 at 300 K. This value is lower than that of Cu 4 TiSe 4 (k L z 0.19 W m −1 K −1 ), which is getting close to the amorphous limit of lattice thermal conductivity. 79 The inclusion of additional four-phonon scattering rates 80 and considering various other phonon scattering mechanisms may further reduce the calculated k L within this family of compounds. Therefore, the amorphous k L and anharmonic nature of these materials necessitate a particle-like phonon treatment, 81 an exciting topic for future research.…”
Section: Lattice Thermal Transportmentioning
confidence: 99%
“…As stable clusters, superatoms have atomic-like electronic structures, which can be qualitatively described by the Jellium model, and the electrons are located in the superatomic molecular orbitals (SAMOs) called 1S, 1P, 1D, 2S, etc. Over the past decades, a large number of superatoms have been discovered, predicted, and even synthesized, ,, suggesting that superatoms, as artificial units, have an important prospect of replacing chemical elements and overcoming some limits of natural elements. , Furthermore, superatoms have been gradually prepared on a large scale, which is an important milestone for superatoms acting as new building blocks of functional materials. , These advantages of superatoms different from natural atoms and nanoparticles are important for us to tune the interlayer spacing of graphene at the atomic level. Particularly for metal clusters, small-sized superatoms have received widespread attention owing to their nonbulk-like and size-specific properties. Among them, a representative example is Au 20 superatom with high structural and chemical stability. It is a pyramid structure with excellent stability owing to its close electron shells. , Previous studies have shown that Au 20 superatoms can be prepared on a large scale. , Therefore, it is very promising to tune the interlayer spacing of graphene to meet functional requirements using the advantages of coinage metal superatoms.…”
Section: Introductionmentioning
confidence: 99%
“…The results are plotted in Figure c, where imaginary acoustic phonon modes are found around the high-symmetry point Y at the harmonic level, which resemble the soft phonon modes in the paraelectric phase of ferroelectric materials like SrTiO 3 , and SnSe, indicating that penta-SrP 2 is dynamically unstable at 0 K. However, by considering the renormalization of anharmonic effects within the scheme of SCP theory, the imaginary phonon modes are suppressed at finite temperature, and they vanish at temperature above 500 K. It is worth mentioning that there are some minor imaginary phonon modes in the vicinity of the high-symmetry point Γ at each finite temperature from 100 to 800 K. These imaginary phonon frequencies of the out-of-plane acoustic branches represent the rippling of the penta-SrP 2 sheet rather than dynamical instability or numerical error, as is the case in hexagonal nitride monolayers . Thus, similar to other reported systems, , the penta-SrP 2 sheet with the type-1 pentagonal tiling geometry is dynamically stable at high temperature.…”
mentioning
confidence: 96%